KARAKTERISTIK BEBAN KENDARAAN OPERASIONAL - Erwin Kusnandar (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
Engineering development and the paradigm of truck operators, who consider that transportation efficiency can be means trucks can carry goods as many as possible in one single trip, can change the engineering characteristics of vehicles, including form, dimension, and vehicle ability increasing speed, and load capacity. The changes in engineering parameters of the operating vehicle will affect the road design parameters in the road design specification. As a result, the road design produced is not optimum, as required by the need to accommodate vehicle’s movement and load, because it can be over or under design, which finally affect the vehicle speed and possibility of the accident occurrence. In this study, the design parameters contributed by operating traffic are compared with those in the existing technical guidance. The results show that there is a significant difference in those parameters, particularly for trucks with three axles. Keyword : Design parameter, Road destroyer factor, overloading.